Pictionary dalam Penguasaan Kosakata Bahasa Jerman - Nurazizah Nurazizah; Laelah Azizah; Nurming Saleh (Academic : Journal of Social and Educational Studies, 2023)
Abstract. This study aims to determine the planning, implementation and results of the application of Pictionary media in mastering German vocabulary for class XI students of SMAN 10 Bulukumba.  This research is a classroom action research which consists of two cycles.  The data presented in this study are quantitative data and qualitative data.  Quantitative data was obtained from the German vocabulary mastery test in cycle 1 and cycle 2, and qualitative data was obtained from observations and then analyzed using the percentage technique.  The results showed that the students' vocabulary mastery in cycle 1 reached a percentage value of 47.17% and increased to 58.41% in cycle 2. These results indicate that the application of Pictionary media increases the mastery of German vocabulary in class XI students of SMAN 10 Bulukumba.  Keywords: Learning Media, Vocabulary Mastery, Pictionary.